Design optimization of an additively manufactured prototype recuperator for supercritical CO2 power cycles. (15th July 2022) - Robey, Ed; Ramesh, Sridharan; Sabau, Adrian S.; Abdoli, Abas; Black, James; Straub, Doug; Yip, Joe
Abstract: Supercritical CO2 (sCO2 ) power cycles are being developed due to their potential for high efficiency and reduced capital cost. It is necessary that these recuperators operate at high pressures and temperatures, up to 30 MPa and 900 K, with effectiveness values > 95% and pressure drops <1% to achieve high cycle efficiencies. Moreover, it is also necessary to have reasonable cost recuperators to control the capital costs of the sCO2 power cycles. In this study, a Plate Pin-Fin (PPF) heat exchanger has been proposed as an sCO2 recuperator. This preliminary recuperator design leverages capabilities enabled by additive manufacturing. Although the PPF design has characteristics similar to those of a plate heat exchanger, small diameter and relatively long fins are used to increase surface area, enhance heat transfer, and provide structural support for the partition plates that separate the fluid streams. Existing correlations for heat transfer and pressure drop were adapted for the PPF heat exchanger. These correlations were implemented in a 1D analytical model and used for the optimization of a 5-kWth high temperature recuperator for an indirect sCO2 cycle by varying the design parameters to minimize the quantity of material required. A 3D conjugate heat transfer numerical simulations were conducted to validate the heat transfer and pressure loss correlations. A steepest descent method was used to minimize heat exchanger mass for a 5-kW prototype recuperator subject to a maximum specified pressure drop. The design analysis indicated that an optimum PPF recuperator would be attained for the minimum allowable pin transverse spacing, minimum pin width, minimum pin height and near maximum cell aspect ratio. At a low material requirement of 0.216 kg/kW and a pressure drop, which is almost five times lower than the allowable pressure drop design target, the optimized PPF heat exchanger has the high potential to be an alternative to a printed circuit heat exchanger, which is a conservative design basis for the current state-of-the-art sCO2 recuperators. Highlights: Novel Plate Pin Fin Heat Exchanger for indirect sCO2 power cycle has been designed. Design is enabled by AM and constrained based on current AM feature resolutions. Mass of a 5 kW HX was minimized subject to maximum specified pressure drop. Optimal 5 kW PPF HX has a low material requirement of 0.216 kg/kW. Optimal PPF has a pressure drop that is about five times lower than design target.